Sexual and gender-based violence and torture experiences of Sudanese refugees in Northern Uganda: health and justice responses - Liebling, Helen Jane; Barrett, Hazel Rose; Artz, Lillian (International journal of migration, health and social care, 2020)
Purpose This British Academy/Leverhulme-funded research (Grant number: SG170394) investigated the experiences and impact of sexual and gender-based violence (SGBV) and torture on South Sudanese refugees’ health and rights and the responses of health and justice services in Northern Uganda. Design/methodology/approach It involved thematic analysis of the narratives of 20 men and 41 women refugees’ survivors of SGBV and torture; this included their experiences in South Sudan, their journeys to Uganda and experiences in refugee settlements. In total, 37 key stakeholders including health and justice providers, police, non-government and government organisations were also interviewed regarding their experiences of providing services to refugees. Findings All refugees had survived human rights abuses carried out in South Sudan, on route to Uganda and within Uganda. Incidents of violence, SGBV, torture and other human rights abuses declined significantly for men in Uganda, but women reported SGBV incidents. The research demonstrates linkages between the physical, psychological, social/cultural and justice/human rights impact on women and men refugees, which amplified the impact of their experiences. There was limited screening, physical and psychological health and support services; including livelihoods and education. Refugees remained concerned about violence and SGBV in the refugee settlements. While they all knew of the reporting system for such incidents, they questioned the effectiveness of the process. For this reason, women opted for family reconciliation rather than reporting domestic violence or SGBV to the authorities. Men found it hard to report incidences due to high levels of stigma and shame. Research limitations/implications Refugees largely fled South Sudan to escape human rights abuses including, persecution, SGBV and torture. Their experiences resulted in physical, psychological, social-cultural and justice effects that received limited responses by health and justice services. An integrated approach to meeting refugees’ needs is required. Practical implications The authors make recommendations for integrated gender sensitive service provision for refugees including more systematic screening, assessment and treatment of SGBV and torture physical and emotional injuries combined with implementation of livelihoods and social enterprises. Social implications The research demonstrates that stigma and shame, particularly for male refugee survivors of SGBV and torture, impacts on ability to report these incidents and seek treatment. Increasing gender sensitivity of services to these issues, alongside provision of medical treatment for injuries, alongside improved informal justice processes, may assist to counteract shame and increase disclosure. Originality/value There is currently a lack of empirical investigation of this subject area, therefore this research makes a contribution to the subject of understanding refugees’ experiences of SGBV and torture, as well as their perceptions of service provision and response. This subject is strategically important due to the pressing need to develop integrated, gendered and culturally sensitive services that listen to the voices and draw on the expertise of refugees themselves while using their skills to inform improvements in service responses and policy.